(untitled) (Revista Inclusiones, 2020)
The Spanish Orientalism and its tributary, which were not a sufficient subject for numerous scientific reviews. The aim of the study is explaining the role of Muslims in the development of Al-Andalus in the period (711–1492), and how it was characterized by Orientalism. We adopted the historicalsystemic method for studying the necessary integral historical objects and phenomena of the Iberian Territory under Islamic administrations in the VIII–XV centuries. Spanish Orientalism was created in order to study the role of the Muslim capture and Islamic upbringing in this territory and its consequences. It turned out that there are three directions of Spanish Orientalism: positive, negative and neutral. In our opinion, we confirm that Al-Andalus, in fact, was characterized by a list of achievements that made a significant contribution to the development of different science in the West. Al-Andalus scholars also developed technological innovations such as windmills and new technologies in crafts such as metal processing, weaving and construction.